Integrating socio-economic support into drug-resistant TB care to optimise treatment outcomes - J. Limo; C. Pahe; I. Kathure; L. Ndungu; A. Mahihu; C. Mwashumbe; E. Mueni; H. Momanyi (IJTLD Open)
BACKGROUND: Drug-resistant TB (DR-TB) remains a public health concern in Kenya, with an estimated 2,500 individuals acquiring DR-TB annually. Despite significant progress in DR-TB management, the treatment success rate (TSR) in 2021 stood at 77%, falling short of the 85% target. This low TSR occurs amidst a complex range of treatment challenges, including psychosocial factors. The aim of this study was to assess the impact of integrating psychosocial and economic empowerment interventions into standard DR-TB care. METHODS: A convergent mixed-method approach was employed, involving interviews with 217 participants, including persons with DR-TB and key stakeholders, using a structured questionnaire. The study was conducted in Kenya’s two highest DR-TB burden counties between October and November 2023. RESULTS: The study found that 55% of respondents experienced psychological depression during treatment, with financial constraints identified as the primary trigger (70.6%). Only 49% of persons with DR-TB joined psychosocial support groups, and of these, 90% demonstrated improved treatment adherence. Additionally, individuals with DR-TB who participated in income-generating activities had a treatment adherence rate of 95%, compared to 88% among those not engaged in such activities. CONCLUSION: Patient-centred approaches involving socio-economic support systems are crucial in addressing treatment adherence barriers, thereby leading to improved treatment outcomes.